Perceived Job Performance and Constraints Hindering Performance of Krishi Vigyan Kendras in Mizoram - P. Lalhmachhuana; Loukham Devarani (Indian Journal of Extension Education, 2017)
The effectiveness of any organisation depends on the performance of the manpower engaged. This study was conducted in three KVKs of Mizoram viz., Kolasib, Lunglei and Aizwal with the objective to assess the perceived job performance of the scientific and technical staff of the KVKs and constraints faced by the staff which hinder their performance. Majority (66.67%) of staff were found to be in medium job performance category. Performance was found to be most effective in presenting and discussing field problems to farmers, conducting need based training programmes, attending official meetings regularly and communicating solutions to farmers on field problems but found to be low in getting samples tested (fertilizers /plant protection chemical /seed / soil & water), providing advisory through ICT and ensuring that rural youths member within the KVK got a stable and reliable job. No special budgetary provision for conduct of demonstration units, delay in releasing salary and lack of man power were the major constraints reported.